COMPARATIVE CHARACTERISTICS OF BIOMORPHOLOGICAL INDICATORS OF TWO HERDS OF ONCORHYNCHUS MYKISS TROUT CULTIVATED ON THE ISSYK RIVER (BALKASH BASIN; REPUBLIC OF KAZAKHSTAN) (Experimental biology, 2022)
Mycizha Oncorchynchus mykiss (Walbaum, 1792) is one of the most common aquaculture objects in the world. Previously, the rainbow trout was considered as an independent species of Salmo gairdenri, but now it is considered to be the European form of the mikizhi.Mycorhynchus mykiss has been cultivated in the world for many centuries and is an ideal option for the sustainable use of water resources in mountainous regions, since both surface and underground waters are suitable for this purpose here. Mikizha breeding began with concrete ponds in 1970 (Kanyurt, 1977 and 1978). At later stages, the cage culture developed in lakes and dammed lakes, which in 1990 were suitable for trout cultivation. Trout breeding also began in the Black Sea in the early 1990s with the help of cages (Sakhin et al., 1999). Trout cultivation can be considered as production in hatcheries, cultivation in inland waters and marine culture. Most trout farms are pond farms within the country.In comparison with European populations, the variability of all studied indicators is at a very high level, which is due to the lack of selection and the large adaptive potential of the herd.
Keywords: Trout; Cultivation; herds; biomorphology; research; comparison